Regulatory framework for the management of cotton weevil (Anthonomus grandis Boheman) in Colombia - Sierra-Monroy, Janeth Alexandra; Burbano-Figueroa, Oscar (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Regulation and enforcement of pest control measures related to cotton production have been regulated for more than 70 years, even before ICA (currently the government agency responsible for crop sanitation) was created. The cotton boll weevil is one the most representative cases of pest control in the Colombian agriculture and also a disappointing experience of failed implementation of control measures that ignored environmental and socioeconomic obstacles. From a regulatory perspective, the control of the boll weevil is an opportunity for assessing how the normative framework has changed through time with the aim to reach a better control. This review also provides alternatives for improving the normative framework related to the cotton boll weevil.